The Effect of Social Media on Youth in The Digital Era - Dedeh Sundarsih; Sri Sudiarti (Majalah Bisnis & IPTEK, 2023)
This research aims to analyze social media's influence on forming Pancasila's character among adolescents in the digital era. The research utilizes a quantitative approach with a survey method and simple random sampling of 100 active social media users among teenagers in Tasikmalaya. The collected data is analyzed using linear regression. The research findings indicate a significant correlation between social media usage and forming of Pancasila characters among adolescents in the digital era. The more frequently teenagers use social media, the lower their Pancasila character tends to be. Additionally, the type of social media users also has varying effects on forming Pancasila's character. Teenagers frequently use social media platforms focused on physical appearance and lifestyle and tend to have lower Pancasila characteristics. This research contributes to the development of theories regarding social media's influence on forming Pancasila's character among adolescents. The results can be a reference for parents and teachers in supervising teenagers' social media usage and cultivating a stronger Pancasila character.